For this case we must simplify the following expression:
[tex](2-7i) (- 1 + 4i)[/tex]
Applying distributive property we have:
[tex](2) (- 1) + (2) (4i) + (- 7i) (- 1) + (- 7i) (4i) =[/tex]
We have to:
[tex]+ * - = -\\- * - = +[/tex]
So:
[tex]-2 + 8i + 7i-28i ^ 2 =[/tex]
We add similar terms:
[tex]-2 + 15i-28i ^ 2 =[/tex]
By definition we have:[tex]i ^ 2 = -1[/tex]
[tex]-2 + 15i-28 (-1) =\\-2 + 15i + 28 =[/tex]
Different signs are subtracted and the sign of the major is placed:
[tex]26 + 15i[/tex]
Answer:
[tex]26 + 15i[/tex]